Gene expression profiling of breast tumours from New Zealand patients - Muthukaruppan, Anita; Lasham, Annette; Blenkiron, Cherie; Woad, Kathryn J.; Black, Michael A.; Knowlton, Nicholas; McCarthy, Nicole; Findlay, Michael P.; Print, Cristin G.; Shelling, Andrew N. (New Zealand Medical Association, 2017)
AIMS: New Zealand has one of the highest rates of breast cancer incidence in the world. We investigated the gene expression profiles of breast tumours from New Zealand patients, compared them to gene expression profiles of international breast cancer cohorts and identified any associations between altered gene expression and the clinicopathological features of the tumours.